Reduction of ephrin-A5 aggravates disease progression in amyotrophic lateral sclerosis - Rué, Laura; Oeckl, Patrick; Timmers, Mieke; Lenaerts, Annette; van der Vos, Jasmijn; Smolders, Silke; Poppe, Lindsay; de Boer, Antina; Van Den Bosch, Ludo; Van Damme, Philip; Weishaupt, Jochen H.; Ludolph, Albert C.; et al. (Acta Neuropathologica Communications, 2019)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease that affects motor neurons in the brainstem, spinal cord and motor cortex. ALS is characterized by genetic and clinical heterogeneity, suggesting the existence of genetic factors that modify the phenotypic expression of the disease. We previously identified the axonal guidance EphA4 receptor, member of the Eph-ephrin system, as an ALS disease-modifying factor. EphA4 genetic inhibition rescued the motor neuron phenotype in zebrafish and a rodent model of ALS. Preventing ligands from binding to the EphA4 receptor also successfully improved disease, suggesting a role for EphA4 ligands in ALS. One particular ligand, ephrin-A5, is upregulated in reactive astrocytes after acute neuronal injury and inhibits axonal regeneration. Moreover, it plays a role during development in the correct pathfinding of motor axons towards their target limb muscles. We hypothesized that a constitutive reduction of ephrin-A5 signalling would benefit disease progression in a rodent model for ALS. We discovered that in the spinal cord of control and symptomatic ALS mice ephrin-A5 was predominantly expressed in neurons. Surprisingly, reduction of ephrin-A5 levels in SOD1G93A mice accelerated disease progression and reduced survival without affecting disease onset, motor neuron numbers or innervated neuromuscular junctions in symptomatic mice. These findings suggest ephrin-A5 as a modifier of disease progression that might play a role in the later stages of the disease. Similarly, we identified a more aggressive disease progression in patients with lower ephrin-A5 protein levels in the cerebrospinal fluid without modifying disease onset. In summary, we identified reduced expression of ephrin-A5 to accelerate disease progression in a mouse model of ALS as well as in humans. Combined with our previous findings on the role of EphA4 in ALS our current data suggests different contribution for various members of the Eph-ephrin system in the pathophysiology of a motor neuron disease.
Gesehen am 17.06.2021